CRITICAL ANALYSIS OF EXPERIMENTAL RESEARCH METHODS AND FACTORS AFFECTING THE BOND BETWEEN REINFORCEMENT AND CONCRET - Dmytrenko, Yevhen; Usenko, Mykola; Pylypaka, Olexander; Bakay, Timofii; Yakovenko, Ihor (Theory and practice of design, 2025)
Purpose. The purpose of this study is to conduct a systematic critical analysis of existing experimental methods (pull-out and beam tests) for studying the bond of reinforcement with concrete, systematization of numerous determining factors (in- cluding the properties of concrete and reinforcement, environmental conditions, ge- ometric and dynamic parameters) on the strength and nature of bond failure, as well as justifying the need to use modern monitoring techniques (DFOS and DIC) to im- prove the reliability of the bond–slip model under conditions of varying types of rebar confinement in the concrete matrix. Methodology. The study is based on a critical analysis and comparison of traditional experimental methods (pull-out/push-in tests and beam tests/beam end tests), which are fundamental for determining average and local bond stresses. The influence of material factors (concrete class, reinforcement diameter), geometric fac- tors (anchorage length, concrete cover, confinement, casting conditions), and en- vironmental/dynamic factors (corrosion, temperature, loading rate) has been sys- tematized. The key methodological approach is to analyze the potential of the latest monitoring techniques: distributed fiber optic sensing (DFOS) and digital image cor- relation (DIC). Results. It has been found that pull-out tests create an unrepresentative stress- strain state (concrete compression) and often give overestimated bond strength values, especially in specimens without a bond-free zone. In contrast, beam tests (in particular, the fib Model Code 2020 modification) better reflect the behavior of reinforcement in the tension zone of elements. DFOS and DIC allow accurate calcu- lation of local parameters τbond and δ, providing external validation of data and con- trol of fracture kinematics. It has been established that increasing the anchorage length (e.g., from 5Ø to 10Ø) leads to a decrease in the average bond strength (up to 32%). Well-confinement of rebar in concrete prevents brittle splitting, promoting plastic pull-out failure, which is better described by the τbond – δ analytical models recommended by current building codes. Corrosion (over 6%) and high temperatures significantly reduce bond strength, while high loading rates (dynamic effects) can in- crease it (dynamic factor of increase DIF ≈ 1.5). Scientific novelty. The scientific novelty lies in the systematic critical synthesis of the multifactorial problem of bond, which highlights the limitations of traditional experimental databases and justifies the synergistic use of DFOS and DIC as a key tool for obtaining detailed local data. These data are necessary for mechanistically justified refinement of the parameters of the bond – slip model under conditions that correspond to operational ones (taking into account the influence of confinement, technological, dynamic, and corrosion effects). Practical relevance. A critical analysis of existing traditional testing methods allows the development of new, more advanced methods for experimental studies of the bond between reinforcement and concrete. The conclusions regarding the feasi- bility of testing methods and influencing factors create a reliable experimental basis for the development of improved numerical and analytical models of bond, which will ultimately increase the reliability of calculations of crack width, anchoring, and de- velop sound recommendations for the renovation and reinforcement of buildings and structures.